2014
DOI: 10.1007/s10499-014-9829-8
|View full text |Cite
|
Sign up to set email alerts
|

A new integrated multi-trophic aquaculture system consisting of Styela clava, microalgae, and Stichopus japonicus

Abstract: The possibility of the integrated multi-trophic aquaculture (IMTA) model consisting of Styela clava, microalgae, and Stichopus japonicus was examined in this research, in which microalgae could remove dissolvable nutrients produced by S. clava and S. japonicus to maintain the dissolvable nutrients at a lower level, and provide sufficient dissolved oxygen in the water body through photosynthesis at the same time. S. clava helped accumulate organic matter in the sediments, and the content of total organic carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In that study, fish effluents in microalgae raceways were diluted with a dilution rate of 70% ± 10% per day (much higher than our study) to reduce total ammonia concentrations; the microalgae in raceways removed 67% (21.3 mg N m -2 d -1 ) NH 4 -N and 46.6 % (2.8 mg P m -2 d -1 ) PO 4 -P. In a recent study using microalgae photo-bioreactors to treat tilapia RAS effluent, Michels et al (2014) found when extra phosphate was added into the wastewater, the N removal efficiency was improved from 49.4 % to 99.7 % (the P removal efficiency was always more than 99 %). More recently, a IMTA system combining the tunicate Styela clava and the sea cucumber Stichopus japonicus removed 54% of dissolved inorganic nitrogen (DIN) and 50% of PO 4 -P, keeping the nutrients at low levels (i.e., C DIN < 0.2 mg L -1 and C P < 0.02 mg L -1 ) (Ju et al, 2015). IMTA system was indoors and the Styela clava concentration was kept at low level, around 200-300 ind.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, fish effluents in microalgae raceways were diluted with a dilution rate of 70% ± 10% per day (much higher than our study) to reduce total ammonia concentrations; the microalgae in raceways removed 67% (21.3 mg N m -2 d -1 ) NH 4 -N and 46.6 % (2.8 mg P m -2 d -1 ) PO 4 -P. In a recent study using microalgae photo-bioreactors to treat tilapia RAS effluent, Michels et al (2014) found when extra phosphate was added into the wastewater, the N removal efficiency was improved from 49.4 % to 99.7 % (the P removal efficiency was always more than 99 %). More recently, a IMTA system combining the tunicate Styela clava and the sea cucumber Stichopus japonicus removed 54% of dissolved inorganic nitrogen (DIN) and 50% of PO 4 -P, keeping the nutrients at low levels (i.e., C DIN < 0.2 mg L -1 and C P < 0.02 mg L -1 ) (Ju et al, 2015). IMTA system was indoors and the Styela clava concentration was kept at low level, around 200-300 ind.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton (live foods) which is eaten by zooplankton forms the basis of the food chain [19]. Moreover, [39] examined the possibility of the integrated multi-trophic aquaculture (IMTA) model consisting of Styela clava , microalgae, and Stichopus japonicus , in which microalgae could remove dissolvable nutrients produced by S. clava and S. japonicus to maintain the dissolvable nutrients at a lower level, and provide sufficient dissolved oxygen in the water body through photosynthesis at the same time. Additionally, live foods contain all the essential nutrients including protein, vitamins, and minerals together with essential PUFAs which are transferred through the food chain [53] and consequently, are commonly known as “living capsules of nutrition”.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, allied with the filtration process is particle retention efficiency. Various approaches have shown that the diet of ascidians mainly comes from smaller particles [particulate organic matter (POM) < 20 µm] (Ju et al, 2015(Ju et al, , 2016, picophytoplankton (<2 µm), and phytoplankton biomass (Riisgärd and Larsen, 2016). Moreover, Lacoste et al (2016) verified an overall lack of food selectivity.…”
Section: Ascidians As Organic Matter Extractive Speciesmentioning
confidence: 99%
“…This biofouling ascidian, with a fast-growing rate (Ramsay et al, 2008b, Lutz-Collins et al, 2009, that contributes to organic sedimentation (Guyondet et al, 2016), and prefers unfouled sites, dark and sheltered areas (Paetzold et al, 2012) does not necessarily have negative impacts on all bivalves or other organisms, further research is needed. Recently, some studies investigated the impacts of the presence of ascidian S. clava in an IMTA framework to optimize the growth of the sea cucumber A. japonicus (Zhen et al, 2014;Ju et al, 2015Ju et al, , 2016. These studies have shown that an IMTA framework consisting of ascidiansea cucumbers-microalgae, not only has the potential to reduce organic matter in the surrounding sediment (Ju et al, 2015), it can also reduce harmful bacteria (Lin et al, 2016) and purify the water body from dissolved nutrients such as nitrogen and phosphorus (Ju et al, 2015).…”
Section: Ascidians Incorporated In Integrated Multi-trophic Aquacultu...mentioning
confidence: 99%